Regulation of Memory Formation by the Transcription Factor XBP1 - Martínez, Gabriela; Vidal, René L.; Mardones, Pablo; Serrano, Felipe G.; Ardiles, Alvaro O.; Wirth, Craig; Valdés, Pamela; Thielen, Peter; Schneider, Bernard L.; Kerr, Bredford; Valdés, Jose L.; Palacios, Adrian G.; et al. (Cell reports (Cambridge), 2016)
Contextual memory formation relies on the induction of new genes in the hippocampus. A polymorphism in the promoter of the transcription factor XBP1 was identified as a risk factor for Alzheimer’s disease and bipolar disorders. XBP1 is a major regulator of the unfolded protein response (UPR), mediating adaptation to endoplasmic reticulum (ER) stress. Using a phenotypic screen, we uncovered an unexpected function of XBP1 in cognition and behavior. Mice lacking XBP1 in the nervous system showed specific impairment of contextual memory formation and long-term potentiation (LTP), whereas neuronal XBP1s overexpression improved performance in memory tasks. Gene expression analysis revealed that XBP1 regulates a group of memory-related genes, highlighting brain-derived neurotrophic factor (BDNF), a key component in memory consolidation. Overexpression of BDNF in the hippocampus reversed the XBP1-deficient phenotype. Our study revealed an unanticipated function of XBP1 in cognitive processes that is apparently unrelated to its role in ER stress. [Display omitted] •Cognitive processes activate the IRE1 branch of the UPR pathway in the hippocampus•The UPR transcription factor XBP1 controls learning and memory-related processes•Enforced expression of XBP1s in the hippocampus improves spatial memory•XBP1 controls synaptic plasticity-related genes, including the expression of BDNF Using gain- and loss-of-function approaches, Martinez et al. demonstrate that XBP1, a master regulator of the unfolded protein response (UPR), regulates learning and memory-related processes. This function of XBP1 in the nervous system involves the control of BDNF expression in the hippocampus.